Preparation method of cationic-π type coating modified carbon fiber and carbon fiber composite material

By introducing a cation-modified polyethylene glycol coating on the surface of carbon fiber, the pi electron system of carbon fiber is used to interact with cations, which solves the problem of insufficient mechanical properties of carbon fiber composite materials and significantly improves the bonding between carbon fiber and resin matrix. .

CN115926141BActive Publication Date: 2025-01-21CHANGCHUN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211479187.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-24
Publication Date
2025-01-21
Estimated Expiration
2042-11-24

AI Technical Summary

Technical Problem

The mechanical properties of carbon fiber composites are insufficient, mainly due to the smooth surface of carbon fiber, which leads to poor interfacial bonding with the matrix.

Method used

Cation-π coating is used to modify carbon fiber. By introducing a cation-modified polyethylene glycol coating on the surface of the carbon fiber, the π electron system of the carbon fiber is used to interact with the cations to improve the bonding between the carbon fiber and the resin matrix.

Benefits of technology

The mechanical properties of carbon fiber composite materials are significantly improved, including interlaminar shear strength and bending strength, and the problem of poor interface bonding is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115926141B_ABST
    Figure CN115926141B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a cation-π type coating modified carbon fiber and a carbon fiber composite material, and belongs to the field of carbon fiber composite materials. The invention aims to solve the problem of chemical inertness on the surface of carbon fiber. The invention introduces a benzene ring by transesterifying a polyhydroxy quaternary ammonium salt with phthalic anhydride, and then reacts with polyethylene glycol to obtain a cation-modified polyethylene glycol compound by drying. The carbon fiber is impregnated with an aqueous solution of a cation-modified polyethylene glycol compound to coat the carbon fiber, that is, a cation-π type coating is introduced on the surface of the carbon fiber. The method of the invention has a simple preparation process, no complicated process and high-energy consumption equipment, and has good application prospects. The cation-π interaction force is introduced between the carbon fiber and the resin in the form of a coating, and the mechanical properties of the carbon fiber are maximized without destroying the mechanical properties of the carbon fiber itself, and the binding between the carbon fiber and the matrix resin is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of carbon fiber composite materials, and specifically relates to a method for preparing a cation-modified polyethylene glycol and a method for preparing a cation-π type coating modified carbon fiber; and also relates to a method for preparing a carbon fiber composite material. Background Art

[0002] Carbon fiber has the advantages of high strength, high modulus, corrosion resistance, and light weight, and is a good reinforcement for preparing composite materials. However, the smooth surface of carbon fiber is chemically inert, which makes the interface bonding between the fiber and the matrix poor, and the mechanical properties of the composite material cannot meet the needs of advanced applications.

[0003] One of the effective ways to solve this shortcoming is to modify the surface of carbon fiber. A common method is to introduce a sizing agent coating on the surface of carbon fiber to improve the surface activity of carbon fiber and the interfacial compatibility between carbon fiber and resin, and improve the bundling and operability of carbon fiber. At present, the research on carbon fiber coating mainly focuses on modifying the matrix resin or using epoxy system sizing agents, but such methods are more complicated to synthesize and are prone to poor curing during the resin curing process and weak direct bonding with carbon fiber. Summary of the invention

[0004] To solve the above problems, based on the property that the carbon fiber surface has a rich π electron system, the present invention proposes a new cationic-π polymer coating, which makes full use of the chemical bonding between the carbon fiber, the coating and the resin matrix to improve the bonding between the carbon fiber and the resin matrix, and improve the problem of poor interface bonding of carbon fiber composites. Experimental results show that the mechanical properties of the composite materials prepared from the carbon fibers treated with the coating are greatly improved.

[0005] The purpose of the present invention is to provide a method for cation-π type modified carbon fiber. The method of the present invention is based on the chemical properties of the carbon fiber itself, and closely links the carbon fiber and the coating through cation-π interaction without destroying the overall properties of the fiber itself. At the same time, the synthesis steps are simple and no high-energy consumption equipment is used. The compatibility between the carbon fiber and the epoxy resin matrix can be significantly improved, and the mechanical properties of the carbon fiber composite material can be improved.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0007] The present invention provides a method for preparing a cation-modified polyethylene glycol, wherein the preparation method is carried out according to the following steps:

[0008] Step 1, dissolving phthalic anhydride and polyhydroxy quaternary ammonium salt (cationic compound) in N, N-dimethylformamide (DMF), adding 1-methylimidazole, heating to reflux under mechanical stirring in an inert atmosphere, and rotary evaporating after heating to fully remove N, N-dimethylformamide (DMF), and then vacuum drying for at least 24 hours to obtain product A;

[0009] Step 2: dissolve product A and polyethylene glycol (PEG) in N,N-dimethylformamide (DMF), add N,N'-dicyclohexylcarboximide (DCC) and 4-dimethylaminopyridine (DMAP), stir at room temperature for at least 24 hours, then add dropwise into ether for purification at least twice, and vacuum dry to obtain cationic-modified polyethylene glycol.

[0010] It is further defined that in step 1, the polyhydroxy quaternary ammonium salt is bis(2-hydroxyethyl)dimethylammonium chloride, di(hydroxyethyl)methyldodecylammonium chloride, 2,3-epoxypropyltrimethylammonium chloride, bishydroxyethyl bishydroxypropyl stearyl ammonium chloride or N-dodecyl-N,N-bis(2-hydroxyethyl)benzyl ammonium chloride, preferably, the polyhydroxy quaternary ammonium salt is bis(2-hydroxyethyl)dimethylammonium chloride.

[0011] It is further defined that in step 1, heating reflux is performed at 70° C. with mechanical stirring for at least 3 hours, and the stirring speed is 400 rpm to 600 rpm.

[0012] It is further defined that in step one, drying is performed in a vacuum oven at 80 degrees Celsius.

[0013] Further defined, in step 1, 0.5 g to 3 g of phthalic anhydride and 0.5 g to 2.5 g of polyhydroxy quaternary ammonium salt are dissolved in 20 mL to 150 mL of dimethylformamide, and 0.2 mL to 2 mL of 1-methylimidazole is added.

[0014] It is further defined that in step 2, 1.5 g to 2 g of product A and 2 g of polyethylene glycol (PEG) are dissolved in 30 mL of dimethylformamide (DMF), and then 1.236 g to 1.3 g of N, N'-dicyclohexylcarboximide (DCC) is added, and the molar ratio of N, N'-dicyclohexylcarboximide (DCC) to 4-dimethylaminopyridine (DMAP) is (5-20):1.

[0015] It is further defined that step 2 is drying in a vacuum oven at 50 degrees Celsius.

[0016] It is further defined that the stirring speed in step 2 is 400 rpm to 600 rpm.

[0017] The preferred amount of polyhydroxy quaternary ammonium salt added in the present invention is 1.0 g to 2.0 g.

[0018] In the present invention, the added amount of 1-methylimidazole is preferably: 0.5 mL 1-methylimidazole.

[0019] In the present invention, the amount of phthalic anhydride added is: 1.5g-2.0g, and the main purpose of adding phthalic anhydride is to introduce benzene rings into the system. In the present invention, the amount of phthalic anhydride added is controlled to ensure sufficient reaction. A small amount of phthalic anhydride will cause the reaction to proceed insufficiently, leaving excess cationic groups. Excessive addition of phthalic anhydride will cause a large amount of by-products to be produced in the system.

[0020] In the present invention, the preferred amount of dimethylformamide added is 50 mL in order to fully dissolve bis(2-hydroxyethyl)dimethylammonium chloride.

[0021] It is further defined that the molecular weight of the polyethylene glycol in step 2 is 2000-10000, preferably 600, 800, 2000 and 4000, and more preferably 2000.

[0022] In the present invention, the ether is purified 2 to 5 times, preferably 3 times, to obtain a pure final product.

[0023] The present invention provides a method for preparing a cationic-π type coating modified carbon fiber, and the preparation method is completed by the following steps:

[0024] Step 1: Add the cationic modified polyethylene glycol prepared by the above method into water and perform ultrasonic treatment until it is completely dissolved.

[0025] Step 2: immerse the carbon fiber in the solution obtained in step 1, and dry it to obtain the cationic-π type coating modified carbon fiber.

[0026] It is further defined that the mass ratio of the cationic modified polyethylene glycol to water in step 1 is 1:(50-100), preferably: the ratio of cationic modified polyethylene glycol to water is 1.5:100. In the present invention, the ratio of water to product must be strictly controlled. Too little will lead to uneven impregnation of the carbon fiber surface, resulting in hairy phenomenon, affecting the interface adhesion. Excessive amount will lead to too thick coating on the carbon fiber surface, making the fiber bundle stronger, affecting the wettability of the resin.

[0027] It is further defined that the impregnation time in step 2 is 5 min-50 min, preferably 10 minutes to ensure that the carbon fiber surface is completely impregnated.

[0028] Further defined, step 2 is drying at 60°C.

[0029] It is further defined that the carbon fiber used in step 2 is desizing carbon fiber, which may be fabric or the like.

[0030] It is further defined that the carbon fiber is impregnated with the cationic-ππ polyethylene glycol for 5-50 minutes, more preferably 10 minutes to ensure that the surface of the carbon fiber is completely impregnated.

[0031] A carbon fiber composite material uses the cationic-π type coating modified carbon fiber prepared by any of the above methods as a reinforcement.

[0032] In the present invention, the resin selected for the carbon fiber composite material is not limited to epoxy resin. Since the present invention is based on the introduction of rich cationic π interactions between the carbon fiber, the coating and the resin matrix for modification, as long as the resin matrix used contains rich benzene rings, the carbon fiber treated with the coating of the present invention can be used as a reinforcement to prepare a composite material.

[0033] Taking epoxy resin as an example, the preparation method of the carbon fiber composite material in the present invention is a vacuum-assisted molding process. The specific operation is to mix the epoxy resin and curing agent H256 with a mass ratio of 100:32 in a stirrer, and then vacuum evacuate in a vacuum drying oven for 30 minutes for use, place a unidirectional carbon fiber fabric with a size of 12cm×12cm on the mold, glue the conduit and cover the guide net on the carbon fiber surface, and then seal the entire device with a vacuum bag, and then use a vacuum pump to pump the epoxy resin glue into the carbon fiber fabric. Subsequently, cure at 90 degrees Celsius for 2 hours, 1205 degrees Celsius for 2 hours, and finally cure at 150 degrees Celsius for 3 hours to obtain a carbon fiber epoxy resin composite material.

[0034] The present invention introduces a cation-π interaction force between the carbon fiber and the resin matrix to improve the interface binding between the carbon fiber and the resin. A polyhydroxy quaternary ammonium salt is subjected to an ester exchange reaction with phthalic anhydride to introduce a benzene ring, and then reacts with a certain amount of polyethylene glycol, and a cation-modified polyethylene glycol compound is obtained by drying. The carbon fiber is immersed in the above-prepared cation-modified polyethylene glycol compound aqueous solution to coat the carbon fiber, that is, a cation-π type coating is introduced on the surface of the carbon fiber. The method has a simple preparation process, no complicated process and high-energy consumption equipment, and has good application prospects.

[0035] The present invention is designed based on the multi-π electron system of carbon fiber itself, without destroying the mechanical properties of carbon fiber itself, and can maximize the mechanical properties of carbon fiber. The cation-π interaction force is introduced between the carbon fiber and the resin in the form of a coating, which solves the problem of chemical inertness of the carbon fiber surface and effectively improves the bonding between the carbon fiber and the matrix resin.

[0036] Based on the rich benzene ring structure and π electron system on the surface of carbon fiber, a strong cation-π interaction can be formed with cations. This strong binding effect is twice that of electrostatic interaction, which can effectively improve the bonding force between carbon fiber and coating to ensure the bonding between fiber and coating. The epoxy resin molecular chain contains many benzene ring structures, which can form a cation-π interaction with the designed coating in the present invention, so that there is a strong interaction between carbon fiber, coating and resin matrix. On the one hand, it improves the chemical properties of the carbon fiber surface, and on the other hand, it can also improve the interface bonding between carbon fiber and resin.

[0037] In order to further understand the features and technical contents of the present invention, please refer to the following detailed description and drawings of the present invention. However, the attached drawings are only provided for reference and illustration and are not intended to limit the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a scanning electron microscope photo of the unmodified carbon fiber in Comparative Example 1;

[0039] Figure 2 This is a scanning electron microscope photo of the carbon fiber modified with polydopamine in Comparative Example 2;

[0040] Figure 3 is a scanning electron microscope image of a carbon fiber modified with a cationic-π type coating prepared by the method of Example 1;

[0041] Figure 4 is the water contact angle of carbon fiber obtained by different modification methods;

[0042] Figure 5 The interlaminar shear strength of carbon fiber epoxy resin composites prepared by different modification methods;

[0043] Figure 6 Flexural strength of carbon fiber epoxy resin composites prepared by different modification methods. DETAILED DESCRIPTION

[0044] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention.

[0045] The carbon fiber used in the following implementation is desizing carbon fiber. The present invention utilizes the chemical properties of carbon fiber itself, and the type of carbon fiber is not particularly limited. The following embodiment uses Toray PAN-based T300 desizing carbon fiber fabric.

[0046] Example 1: The preparation method of cationic modified polyethylene glycol in this example is carried out according to the following steps:

[0047] Step 1: 1.4 g of phthalic anhydride and 0.8 g of a cationic compound bis(2-hydroxyethyl)dimethylammonium chloride were dissolved in 80 mL of N,N-dimethylformamide (DMF), 0.5 mL of 1-methylimidazole was added, and the mixture was heated to reflux for 3 hours at 70 degrees Celsius and mechanically stirred at 500 rpm in an inert gas (argon) atmosphere. After the heating reflux reaction was completed, the mixture was subjected to 3 rotary evaporations at 145 degrees Celsius in a rotary evaporator to fully remove N,N-dimethylformamide, and the product was dried in a vacuum oven at 80 degrees Celsius for 24 hours to obtain product A.

[0048] Step 2: 1.5 g of the product A obtained in step 1 was added to 2 g of polyethylene glycol (PEG, molecular weight 600) and 30 mL of N, N-dimethylformamide (DMF), and the mixture was stirred at room temperature for 24 hours under mechanical stirring at 500 rpm in the presence of 1.236 g of N, N'-dicyclohexylcarboximide (DCC) and 0.0732 g of 4-dimethylaminopyridine (DMAP). After the reaction, the obtained mixture solution was added dropwise to ether for purification three times, and vacuum dried at 50 degrees Celsius to be labeled as cationic-modified polyethylene glycol.

[0049] The above method is used to prepare cationic polyethylene glycol-modified carbon fibers, which is specifically achieved through the following steps:

[0050] 2 g of the cation-modified polyethylene glycol product prepared by the method of Example 1 was added to 100 mL of water and ultrasonically dissolved to obtain a cationic-π-type coating aqueous solution. Then, a carbon fiber fabric with a size of 12 cm×12 cm was immersed in the cationic-π-type coating aqueous solution for 10 minutes. Finally, the treated carbon fiber was placed in an oven at 60 degrees Celsius for drying to obtain a cationic-π-type coating modified carbon fiber.

[0051] The cationic-π type coating modified carbon fiber prepared by the above method is used to prepare a carbon fiber epoxy resin composite material, and the specific steps are as follows:

[0052] Epoxy resin and curing agent H256 with a mass ratio of 100:32 were mixed evenly in a mixer, and then vacuumed in a vacuum drying oven for 30 minutes for use. The carbon fiber fabric was placed on the mold, the conduit was glued and the guide net was covered on the carbon fiber surface, and then the entire device was sealed with a vacuum bag, and the epoxy resin glue was pumped into the carbon fiber fabric with a vacuum pump. Subsequently, it was cured at 90 degrees Celsius for 2 hours, cured at 120 degrees Celsius for 2 hours, and finally post-cured at 150 degrees Celsius for 3 hours to obtain a carbon fiber epoxy resin composite material.

[0053] Example 2: The preparation method of cationic modified polyethylene glycol in this example is carried out according to the following steps:

[0054] Step 1: 2.0 g of phthalic anhydride and 1.2 g of a cationic compound bis(2-hydroxyethyl)dimethylammonium chloride were dissolved in 80 mL of dimethylformamide, 0.6 mL of 1-methylimidazole was added, and the mixture was heated to reflux at 70 degrees Celsius and mechanically stirred at 500 rpm for 3 hours in an inert gas (argon) atmosphere. After the heating reflux reaction was completed, the mixture was rotary evaporated three times in a rotary evaporator at 145 degrees Celsius, and the product was dried in a vacuum oven at 80 degrees Celsius for 24 hours.

[0055] Step 2: 3 g of the product A obtained in step 1 was added to 2 g of polyethylene glycol (PEG, molecular weight 2000) and 30 mL of dimethylformamide, and the mixture was stirred at room temperature for 24 hours under mechanical stirring at 500 rpm in the presence of 1.3 g of N, N'-dicyclohexylcarboximide (DCC) and 0.075 g of 4-dimethylaminopyridine (DMAP). After the reaction, the obtained mixture solution was added dropwise to ether for purification three times, and vacuum dried at 50 degrees Celsius to be labeled as cationic-modified polyethylene glycol.

[0056] The above method is used to prepare cationic polyethylene glycol-modified carbon fibers, which is specifically achieved through the following steps:

[0057] 2 g of the cation-modified polyethylene glycol product prepared in the above reaction was added to 100 mL of water and ultrasonically dissolved to obtain a cationic-π-type coating aqueous solution. Then, a carbon fiber fabric with a size of 12 cm×12 cm was immersed in the cationic-π-type coating aqueous solution for 10 minutes. Finally, the treated carbon fiber was placed in an oven at 60 degrees Celsius for drying to obtain a cationic-π-type coating modified carbon fiber.

[0058] The cationic-π type coating modified carbon fiber prepared by the above method is used to prepare a carbon fiber epoxy resin composite material, and the specific steps are as follows:

[0059] Epoxy resin and curing agent H256 with a mass ratio of 100:32 were mixed evenly in a mixer, and then vacuumed in a vacuum drying oven for 30 minutes for use. The carbon fiber fabric was placed on the mold, the conduit was glued and the guide net was covered on the carbon fiber surface, and then the entire device was sealed with a vacuum bag, and the epoxy resin glue was pumped into the carbon fiber fabric with a vacuum pump. Subsequently, it was cured at 90 degrees Celsius for 2 hours, cured at 120 degrees Celsius for 2 hours, and finally post-cured at 150 degrees Celsius for 3 hours to obtain a carbon fiber epoxy resin composite material.

[0060] Comparative Example 1:

[0061] After the unidirectional fabric carbon fiber is desizing, it is cut into 12cm×12cm carbon fiber samples, and then the epoxy resin and curing agent H256 with a mass ratio of 100:32 are mixed evenly in a mixer, and then vacuumed in a vacuum drying oven for 30 minutes for use, and the desizing carbon fiber (hereinafter referred to as unmodified carbon fiber) fabric is placed on the mold, the conduit is glued and the guide net is covered on the carbon fiber surface, and then the entire device is sealed with a vacuum bag, and then the epoxy resin glue is pumped into the carbon fiber fabric with a vacuum pump. Subsequently, it is cured at 90 degrees Celsius for 2 hours, cured at 1205 degrees Celsius for 2 hours, and finally post-cured at 150 degrees Celsius for 3 hours to obtain a carbon fiber epoxy resin composite material.

[0062] Comparative Example 2:

[0063] The unidirectional fabric carbon fiber was de-sized and cut into 12 cm×12 cm carbon fiber samples for standby use. 2 g of dopamine was dissolved in 1000 mL of water, and then 2 g of Tris buffer solution was added to the mixture and stirred evenly. The mixture was reacted at room temperature for 6 hours. The obtained carbon fiber was labeled as polydopamine-modified carbon fiber.

[0064] Then, epoxy resin and curing agent H256 with a mass ratio of 100:32 were mixed evenly in a mixer, and then vacuumed in a vacuum drying oven for 30 minutes for use. The polydopamine-modified carbon fiber fabric was placed on the mold, the conduit was glued and the guide net was covered on the carbon fiber surface, and then the entire device was sealed with a vacuum bag, and the epoxy resin glue was pumped into the carbon fiber fabric with a vacuum pump. Subsequently, it was cured at 90 degrees Celsius for 2 hours, cured at 120 degrees Celsius for 2 hours, and finally post-cured at 150 degrees Celsius for 3 hours to obtain a carbon fiber epoxy resin composite material.

[0065] Since polydopamine modified carbon fiber is a commonly used method for carbon fiber surface modification, polydopamine modified carbon fiber was selected for comparison. The principle of polydopamine modified carbon fiber is to introduce phenolic hydroxyl groups and oxygen-containing functional groups on the surface of carbon fiber, which can improve the surface chemical environment of carbon fiber, increase the surface polarity of carbon fiber, and thus improve the interface bonding between carbon fiber and resin matrix.

[0066] The water contact angle of the carbon fiber modified by polydopamine is slightly increased, which is due to the presence of polydopamine on the surface of the carbon fiber, which introduces some polar groups, thereby improving the polarity of the carbon fiber surface. The water contact angle of the carbon fiber modified by the coating in the present invention is significantly reduced, which is due to the fact that the coating involved in the present invention introduces a large number of oxygen-containing functional groups such as ester bonds, carbonyl groups and hydroxyl groups, which can effectively improve the wettability of the carbon fiber surface (see Figure 4 ).

[0067] The interlaminar shear strength of carbon fiber epoxy resin composites prepared by different modification methods is shown in Figure 2. Figure 5 The flexural strength of carbon fiber epoxy resin composites prepared by different modification methods is shown in Figure 6 As shown. Figure 5 and Figure 6 The results show that the cationic-π type coating involved in the present invention can effectively improve the interface bonding between carbon fiber and epoxy resin.

[0068] The descriptions in the above embodiments are only used to better understand the specific processes and features of the present invention. The parameters involved in the embodiments can be adjusted and modified according to the scope of rights limited by the present invention, and all belong to the scope of protection of the present invention.

Claims

1. A method for preparing a cationic-π type coating modified carbon fiber, characterized in that: The preparation method is completed by the following steps: Step 1: Add cationic modified polyethylene glycol into water and perform ultrasonic treatment until it is completely dissolved. Step 2, dipping the carbon fiber into the solution obtained in step 1, and drying to obtain a cationic-π-type coating modified carbon fiber; Wherein, the cationic modified polyethylene glycol is prepared according to the following steps: Step 1, dissolving phthalic anhydride and polyhydroxy quaternary ammonium salt in N,N-dimethylformamide, adding 1-methylimidazole, heating to reflux under mechanical stirring in an inert atmosphere, rotary evaporation after the reaction to fully remove N,N-dimethylformamide, and then vacuum drying for at least 24 hours to obtain product A; Step 2: dissolving product A and polyethylene glycol in N,N-dimethylformamide, adding N,N'-dicyclohexylcarboximide and 4-dimethylaminopyridine, stirring at room temperature for at least 24 hours, then dropping into ether for purification at least twice, and vacuum drying to obtain cationic-modified polyethylene glycol; Dissolve 0.5g-3g of phthalic anhydride and 0.5g-2.5g of polyhydroxy quaternary ammonium salt in 20mL-150mL of dimethylformamide, and add 0.2mL-2mL of 1-methylimidazole; The mass ratio of the cation-modified polyethylene glycol to water in step 1 is 1:(50-100).

2. The preparation method according to claim 1, characterized in that: In step 1, the polyhydroxy quaternary ammonium salt is bis(2-hydroxyethyl)dimethylammonium chloride, di(hydroxyethyl)methyldodecylammonium chloride, 2,3-epoxypropyltrimethylammonium chloride, bishydroxyethyl bishydroxypropyl stearyl ammonium chloride or N-dodecyl-N,N-bis(2-hydroxyethyl)benzyl ammonium chloride.

3. The preparation method according to claim 1, characterized in that: Step 1: Heat to reflux at 70°C for at least 3h.

4. The preparation method according to claim 3, characterized in that: 1.5g~2g of product A and 2g of polyethylene glycol were dissolved in 30mL of dimethylformamide, and then 1.236g~1.3g of N,N'-dicyclohexylcarboximide was added. The molar ratio of N,N'-dicyclohexylcarboximide to 4-dimethylaminopyridine was (5-20):

1.

5. The preparation method according to claim 1, characterized in that: In step 2, the molecular weight of polyethylene glycol is 2000-10000.

6. The preparation method according to claim 1, characterized in that: The immersion time in step 2 is 5 min to 50 min.

7. A carbon fiber composite material, characterized in that the cationic-π-type coating modified carbon fiber prepared by the method of any one of claims 1 to 6 is used as a reinforcement.

Citation Information

Patent Citations

  • Composite material of modified carbon fibers and nanoaramid fibers and preparation method of composite material

    CN108610628A

  • Fiber bundling agent, fiber bundle, molding material, and molded article

    CN114539501A